Approach to the vascular complications of lumbar disc surgery. (April 2013) - Bozok, Sahin; Ilhan, Gokhan; Destan, Bugra; Gokalp, Orhan; Gunes, Tevfik
The objective of this study was to demonstrate the role of major surgery on patients presenting with vascular complications after lumbar disc surgery. A retrospective analysis of seven cases treated surgically in two tertiary care centers between August 2001 and June 2010 was carried out. The average age of patients (three women and four men) was 35.8 ± 7.2. The most common vessel injured was the left common iliac artery occurring in five patients (71.4%), followed by the left common iliac vein injury detected in two patients (28.5%). Transperitoneal approach was preferred in all cases and primary suturing, graft interposition and end-to-end anastomoses were the surgical methods used for the repair of vascular injury. No mortality was seen in our series during the follow-up period of two years; however, the most noteworthy complication was paraplegia occurring in one patient. Vascular injury occurring at lumbar discus surgery has a considerable potential for morbidity and mortality. A high index of suspicion is necessary for early diagnosis. In hemodynamically instable patients, the transperitoneal approach provides better exposure and more effective control of hemorrhage, while minimal angiography and endovascular intervention should be preserved for hemodynamically stable cases.